The Role of Ethnomathematics in Mathematics Learning - Yanti, Ili (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
Ethnomathematics is one of the fields of study of mathematics applied by certain cultural groups. Ethnomathematics is learning based on local culture so that students can simultaneously recognise and explore the culture of their nation. This research aims to find out the role of ethnomathematics in learning mathematics. This research is a type of literature research with a qualitative approach. How to collect data by means of document studies and analysed with descriptive analysis techniques. Library research is research whose data comes from books, documents, magazines, journals and so on. The analysis technique used is descriptive analysis technique by looking at research data that has been carried out by previous researchers related to ethnomathematics research. Based on a review of previous research, the result of this study is that ethnomathematics has many roles in learning mathematics, including: 1) improving mathematical understanding skills, 2) improving students' mathematical abilities, 3) strengthening cultural wisdom in mathematics learning, 4) developing mathematical literacy skills, and 5) developing media for mathematics learning.